The impacts of intellectual capital and entrepreneurship orientation on business performance - Anggraini, Fivi; Yunilma, Yunilma; Desiyanti, Rika; Hakim, Luqmannul (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2023)
The Covid-19 pandemic has systematically impacted all lines, including the hospitality industry, which experienced the lowest occupancy rate. For this reason, innovation is needed for the hotel industry to develop intellectual capital management and be entrepreneurially oriented so that its business can continue to breathe amid the current global pandemic. This study aims to examine the effect of intellectual capital and entrepreneurial orientation on business performance in hospitality tourism in West Sumatra. The population of this study is all-star and non-star hotels registered with the Central Bureau of Statistics of West Sumatra Province. Our results demonstrate that human and structural capital do not significantly affect business performance. Meanwhile, relational capital and entrepreneurial orientation have a significant effect on the performance of the hotel business. The results of this study contribute to knowledge about the relationship of intellectual capital in the hotel business to improve business performance, especially in the current situation of the Covid-19 pandemic.